Direct Visualization of Live Zebrafish Glycans via Single‐Step Metabolic Labeling with Fluorophore‐Tagged Nucleotide Sugars. Issue 40 (28th August 2019) - Hong, Senlian; Sahai‐Hernandez, Pankaj; Chapla, Digantkumar Gopaldas; Moremen, Kelley W.; Traver, David; Wu, Peng
Abstract: Dynamic turnover of cell‐surface glycans is involved in a myriad of biological events, making this process an attractive target for in vivo molecular imaging. Metabolic glycan labeling coupled with bioorthogonal chemistry has paved the way for visualizing glycans in living organisms. However, a two‐step labeling sequence is required, which suffers from the tissue‐penetration difficulties of the imaging probes. Here, by exploring the substrate promiscuity of endogenous glycosyltransferases, we developed a single‐step fluorescent glycan labeling strategy by using fluorophore‐tagged analogues of the nucleotide sugars. Injecting fluorophore‐tagged sialic acid and fucose into the yolk of zebrafish embryos at the one‐cell stage enables systematic imaging of sialylation and fucosylation in live zebrafish embryos at distinct developmental stages. From these studies, we obtained insights into the role of sialylated and fucosylated glycans in zebrafish hematopoiesis. Abstract : Single‐step fluorescent labeling of glycans in live zebrafish is achieved by the metabolic incorporation of fluorophore‐tagged nucleotide sugars. This procedure avoids the problem of the poor tissue penetration of fluorescent probes associated with well‐established two‐step fluorescent labeling procedures.